MENGENAL JENIS HIU APENDIKS II CITES - Fahmi Fahmi (Pusat Penelitian Oseanografi LIPI, 2018)
KNOWING SHARKS LISTED IN APPENDIX II CITES. Sharks have become one of major concerns in fisheries management and marine conservation worldwide. Many members of this group are threatened to extinction due to extensive exploitation since few decades ago. Several species of sharks are now listed in the CITES appendices, which controls the international trade for endangered species. Most of them are relatively easy to identify in the field, especially if their fins are still attached. However, few species may difficult to identify correctly due to the similar appearance to other non-CITES species and when the body is not complete anymore. This article aims to give better understanding on how to identify some shark CITES species in detail.